2016
DOI: 10.1021/acs.bioconjchem.6b00452
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescently Labeled Cyclodextrin Derivatives as Exogenous Markers for Real-Time Transcutaneous Measurement of Renal Function

Abstract: Evaluation of renal function is crucial for a number of clinical situations. Here, we reported a novel exogenous fluorescent marker (FITC-HPβCD) to real-time assess renal function by using a transcutaneous fluorescent detection technique. FITC-HPβCD was designed based on the principle of renal clearance of designed drugs. It displays favorable fluorescent properties, high hydrophilicity, low plasma protein binding, and high stability in porcine liver esterase as well as in plasma and nontoxicity. More importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…The functional state of the kidneys can be assessed by using the glomerular filtration rate (GFR), renal blood flow, and tubular reabsorption or secretion of various substances . Among them, the GFR is often used to evaluate overall renal function and is accepted as the best indicator for kidney function . The GFR represents the plasma volume cleared by the nephrons per time unit during urine formation.…”
Section: Traditional Agents and Determination Methods For The Assessmmentioning
confidence: 99%
See 4 more Smart Citations
“…The functional state of the kidneys can be assessed by using the glomerular filtration rate (GFR), renal blood flow, and tubular reabsorption or secretion of various substances . Among them, the GFR is often used to evaluate overall renal function and is accepted as the best indicator for kidney function . The GFR represents the plasma volume cleared by the nephrons per time unit during urine formation.…”
Section: Traditional Agents and Determination Methods For The Assessmmentioning
confidence: 99%
“…The concentration of endogenous creatinine in plasma is commonly used to determine the GFR (Figure b), but it may result in erroneous estimates due to age, gender, muscle mass, and many other anthropometric variables . Determination of the plasma/urinary clearance of exogenous renal agents such as 99m Tc–DTPA (diethylenetriaminepentaacetic acid, DTPA), inulin, and iothalamate (Figure c) is invasive and cumbersome due to the requirement of multiple blood/urine sampling steps and tedious sample analysis by high‐performance liquid chromatography (HPLC) . Moreover, many studies have revealed that creatinine and iothalamate are secreted by proximal tubule cells, whereas cystatin C and 99m Tc–DTPA are reabsorbed by the tubular epithelial cells, which leads to a bias in the GFR .…”
Section: Traditional Agents and Determination Methods For The Assessmmentioning
confidence: 99%
See 3 more Smart Citations